Lemmatization and sentiment analysis of Greek political tweets during the pre-election period of 2023 - Chantavaridou, Elisavet; Kapidakis, Sarantos (Journal of Integrated Information Management, 2023)
Purpose – The present work discusses findings of a research on Twitter data of the two politicians running for Prime Minister, as well as their press secretaries, during the pre-election period of May 2023 in Greece. Design/methodology/approach – We collected the tweets that were posted by the two main candidates running for Prime Minister in Greece, as well as their press secretaries, during the pre-election period of May 2023. Lemmatization was performed on the four sets of tweets as well as sentiment analysis using SentiStrength for Greek, a sentiment dictionary that was developed for Greek political short text/ tweets. Findings – Results revealed the importance of positive sentiment when posting on Twitter; they also revealed the different approaches of mentioning people vs locations of the two politicians that were running for Prime Minister. Originality/value – Writing positive tweets during a pre-election period can lead to victory in Greece. Focusing excessively on the opponent and other political figures is not a way to win voters in Greece in 2023. Instead, making references to geographic locations in Greece is preferred. Furthermore, SentiStrength for Greek is used for the first time.